Blueberry Varieties for Florida - Jeffrey G. Williamson; Paul M. Lyrene (EDIS)
Blueberries are native to eastern North America. They are one of the few crop plants that originated here. The rabbiteye blueberry (Vaccinium ashei) occurs mostly in certain river valleys in northern Florida and southeastern Georgia. The highbush blueberry (Vaccinium corymbosum) is native in the eastern third of the United States and southeastern Canada. Florida is rich in other native Vaccinium species. The woods and swamps of Florida are populated with at least eight wild blueberry species. No area of the state lacks wild blueberries, except where soil pH is above 6.0. This document is HS967, one of a series of the Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: March 2004.